The Effect of Nutrient Availability and Light Conditions on the Growth and Intracellular Nitrogen Components of Land-Based Cultivated Saccharina latissima (Phaeophyta) - Jevne, Lone Sunniva; Forbord, Silje; Olsen, Yngvar (Frontiers in Marine Science, 2020)
With the increasing interest and activities regarding seaweed cultivation in Europe, it is becoming crucial to utilize the opportunities that lies within environmental resources, such as light and nutrients, to produce biomass of a high yield and quality. The chemical composition of seaweed varies between seasons and depths as an effect of resource supply and environmental conditions. These factors are particularly important to assess for economically feasible species like the kelp Saccharina latissima. This paper examines how differences in light conditions and nutrient availability affect the growth and intracellular nitrogen in S. latissima. This was done through cultivating sporophytes in land-based tanks with four different combinations of high/low light and high/low nutrient supply over an experimental period of 20 days, with measurements of growth rate and subsequent analysis of tissue nitrogen metabolites. The results revealed that the mean growth rate and the intracellular nitrogen components of the sporophytes were positively related to the external nitrate concentration during the experimental period, indicating that S. latissima requires high nutrient concentration to maintain a rapid growth.